Substance use in deliquent adolescents - Ögel, Kültegin; Aksoy, Alper (Journal of Dependence, 2007)
Objective: Generally the studies on deliquent adolescents are conducted in one institution. So, these findings are insufficient to represent the whole deliquent adolescent population over the country. The objective of this study is to determine the prevalence and characteristics of substance use in deliquent adolescents. Method: The sample of the study consist of 270 adolescents, under the age of 18, staying in İstanbul, Ankara, Elazığ, İzmir reformatory and detention centers . The sample is randomly selected. The applied research questionnare developed by Yeniden Health and Education Society. Results: The mean age of the participants were 17.43±0.97. %29.7 of the adolecents stated that while they were commiting a crime, they were under the influence of substances. 29.7% of the deliquent adolescents reported that they were under the influence of substance in their previous crimes. In addition, 32.8% reported that they were under the influence of substances during their last crime which was ended with being arrested and sentenced. In deliquent adolescents, the mean age of committing a crime was 14.2±2.4. Among deliquent adolescents try substances at least once, the mean age of first crime was 13.8±2.6. It was found that generally, substances like tobacco, alcohol and canabis are being used before the crime. Discussion: In conclusion, the prevalence of substance use found to be high in deliquent adolescents. While people are working with deliquent adolescent, they should keep substance use in mind and we believe that they should intervene end treat substance users in the institution.